The impact of total lockdown on Malaysians: A cross-sectional study - Nurhamiza Mumin @ Osman (Human Resource Management Academic Research Society (HRMARS), 2022)
Malaysia has conducted a series of total lockdowns that involved movement restrictions and temporary closure of non-essential industries to curb the spread of the virus. Malaysians have created some degree of normalcy while living with the pandemic. Therefore, this study aimed to identify the most trusted COVID-19 source of information among Malaysians. It will also identify the newly cultivated habits, personal experiences, and the most affected groups during the implementation of the total lockdowns in Malaysia. Data were obtained via an online survey which was administered to 279 willing participants throughout Malaysia. Descriptive analysis was used to investigate the impact of the lockdown on individual stress levels, while Mann-Whitney U and Kruskal-Wallis tests were used to determine whether there were any significant differences in the impact of the lockdown among the respondents involved. The study found physical distance, self-quarantining, and religiously following media coverage have become routine among Malaysians. The study also identified singles, young people, part-time workers, and unemployed people as the most affected groups in terms of income, family conflict, and access to food and mental health treatments. Total lockdowns had the greatest impact on the daily routine of Indians and indigenous ethnic groups of Borneo compared to other groups of people. This study offers some important insights into the effects of total lockdown on different groups of Malaysians. It can also provide critical information to policymakers, government agencies, and researchers in the event of an additional lockdown or a pandemic.